MicroRNAs in spinal cord injury: A narrative review - Zhang, Chunjia; Talifu, Zuliyaer; Xu, Xin; Liu, Wubo; Ke, Han; Pan, Yunzhu; Li, Yan; Bai, Fan; Jing, Yingli; Li, Zihan; Li, Zehui; Yang, Degang; et al. (Frontiers in Molecular Neuroscience, 2023)
Spinal cord injury (SCI) is a global medical problem with high disability and mortality rates. At present, the diagnosis and treatment of SCI are still lacking. Spinal cord injury has a complex etiology, lack of diagnostic methods, poor treatment effect and other problems, which lead to the difficulty of spinal cord regeneration and repair, and poor functional recovery. Recent studies have shown that gene expression plays an important role in the regulation of SCI repair. MicroRNAs (miRNAs) are non-coding RNA molecules that target mRNA expression in order to silence, translate, or interfere with protein synthesis. Secondary damage, such as oxidative stress, apoptosis, autophagy, and inflammation, occurs after SCI, and differentially expressed miRNAs contribute to these events. This article reviews the pathophysiological mechanism of miRNAs in secondary injury after SCI, focusing on the mechanism of miRNAs in secondary neuroinflammation after SCI, so as to provide new ideas and basis for the clinical diagnosis and treatment of miRNAs in SCI. The mechanisms of miRNAs in neurological diseases may also make them potential biomarkers and therapeutic targets for spinal cord injuries.